Sharing economy research: a research agenda for knowledge management scholars - Chua, Alton Yeow Kuan (2023)
Purpose: This paper aims to provide a research agenda for knowledge management (KM) scholars interested in the sharing economy. Design/methodology/approach: A total of 342 articles published between 2012 and 2021 are analysed to identify the topics examined, how the sharing economy was conceptualized, the academic disciplines of authors and the methods used. Findings: Based on the findings, research gaps and conceptualization issues relevant to KM scholars are discussed. Collaboration opportunities and methodological challenges are also identified. Originality/value: By facilitating KM scholars’ engagement with the sharing economy, this paper contributes to a better understanding of this emerging phenomenon and helps uncover potential KM trends.